Study on the home game effect and its influential factors in Chinese shooting competition - Wu, M.; Yin, X. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The earliest study on Home Game Effect (also called Home Advantage) was conducted by Schwartz, et al in 1977. They systematically proved the existence of the `Home Game Effect` through data analysis. This paper, on the basis of the renewed definition of the "Home Game Effect", analyses the phenomenon of `Home Game Effect` in Chinese shooting competition. Moreover, findings from the study will provide some strategies to assist Chinese shooting athletes to achieve better resultst in coming matches, especially the 2008 Olympic Games. Methods A comprehensive literature review was conducted, summarizing research on the `Home Game Effect`. Analysis of how the Home Game Effect influences athletes` performance in competition was observed through the reviewing of games. Statistical analyses of the competition scores of the Chinese shooting team in 2007 was undertaken and some of the coaches, athletes and experts related to the domain were interviewed. Results The study found that, compared with other competitions, there was no obvious `Home Game Effect` in Chinese shooting competitions. The main factors influencing this effect in shooting competitions were psychological characteristics of the athletes, spectators and media. In contrast, other factors such as arena, climate, appliance and referees played a less important role. Discussion / Conclusions Shooting, as a closed competition sport has the characteristic of interpersonal indirect competition. Being a personal item, it requires the ability of mental control to be high. Meanwhile, being a static activity lasting for an extended period of time and for many shots, it requires a high degree of mental stability. The technique of Chinese shooters has reached a high level, but there is no obvious `Home Game Effect` in the events. The main reason for this phenomenon is that shooting calls for the psychological quality of the athletes and the home environment brings great pressure and a tense atmosphere to the athletes, which makes them extremely sensitive to external conditions, such as spectators and media. Furthermore sensitivity to external conditions will probably affect confidence, determination, motivation and emotion negatively and further affect the athletes` performance. Shooting, as a strong sport in China, receives more attention in the country than for other events. When competition is held at home, the excessive attention and expectation paid to the athletes by the spectators and media, brings great psychological pressure, which adversely affects performance. Thus coaches and athletes must try their best to avoid information disturbance from the environment, while improving psychological qualities in order to strive for excellence. There is still a long way to go to change the phenomenon that the `Home Game Effect` in Chinese shooting competitions is not apparent. A mutual contribution by coaches, athletes and researchers needs to be made to achieve this goal.